Multi-Messenger observations of the γ-ray blazar 4FGL J0658.6+0636 consistent with an IceCube high-energy neutrino - de Menezes, Raniere; Buson, Sara; Garrappa, Simone; Gokus, Andrea; Kadler, Matthias; Cheung, Teddy; Giroletti, Marcello; Ajello, Marco; Massaro, Francesco; Peña-Herazo, Harold; Schüssler, Fabian; Bernardini, Elisa; et al. (Proceedings of Science, 2022)
The detection of cosmic neutrinos has raised many new questions in astroparticle physics, among the most compelling of which is the identification of cosmic neutrino emitters. After more than a decade of IceCube operations, the most promising neutrino astrophysical association remains the very-high-energy (VHE, > 100 GeV) blazar TXS 0506+056. Recently, on November 14, 2020 the IceCube observatory reported the detection of a well-reconstructed high-energy neutrino event, IceCube-201114A, with a high probability of being astrophysical. Within the 90% IceCube-201114A localization region only one known γ-ray (> 100 MeV) source is found. This is 4FGL J0658.6+0636, associated with the blazar NVSS J065844+063711. In these proceedings we present results from the rich multi-messenger campaign triggered by the IceCube-201114A neutrino detection, which has allowed us to collect simultaneous and quasi-simultaneous data for the γ-ray source potentially associated with the neutrino. NVSS J065844+063711 is a previously-known blazar with broadband properties resembling a high-synchrotron-peaked object, making it a promising TeV emitter. Indeed, the detection of very high-energy (VHE) photons (i.e., > 100 GeV) by the Fermi Large Area Telescope provides the first evidence of such emission from this object. It makes NVSS J065844+063711 the second VHE object found within the 90% confidence region of a well-reconstructed, high-energy IceCube event.
CRIS-Team Scopus Importer:2024-12-16